KUALITAS FRONT OFFICE DALAM MENINGKATKAN PELAYANAN DI RUMAH SAKIT - Neneng Irmawati (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
Hospitals meet the needs and demands of patients who expect the resolution of health problems because hospitals are considered capable of providing comfortable, fast, and responsive medical services to their patients. Hospitals that provide excellent service to their patients will get more value in the environment and the surrounding community. Patient satisfaction can be influenced by the provision of information provided by the hospital to its visitors. Improving the quality of service can increase profits and the hospital market. To provide maximum service, the hospital can provide a special place or officer to provide information. Because there is a front office service at the very front. Front office which is the central part that serves as the heart of all activities ranging from providing information. Therefore, the presence of front office staff is at the forefront of service at the hospital, which is required to be friendly, communicative and well-spoken and confident in serving visitors. This study is research on the quality of front office services in hospitals. This study was also conducted to find out how the responsibility of hospital front office officers in serving their patients. This research was conducted descriptively with direct observation. This study is presented to obtain information related to the provision of hospital front office services to visitors or patients. The method used in this study using the servqual and canoe methods, data collection was carried out using field studies and literature studies. The results showed that there was an influence between reliability, responsiveness, assurance, empathy and tangibles on patient satisfaction, meaning that if reliability, responsiveness, Assurance, empathy and physical evidence (tangibles) increase, patient satisfaction will increase.